Refractory thoracic endometriosis syndrome with bilateral hemothorax. Issue 7 (15th May 2017) - Lua, Lannah L.; Tran, Kevin; Desai, Jyoti
Abstract: Thoracic endometriosis syndrome (TES) is a rare disorder presenting with catamenial pneumothorax, hemothorax, hemoptysis or pulmonary nodules. Bilateral involvement is uncommon, and only a very few cases have been reported in the literature. We report a case of bilateral catamenial hemothorax in a patient with recurrent thoracic endometriosis. Despite multiple surgical interventions, the patient continued to develop hemopneumothorax coinciding with menses. Remission was finally achieved with the addition of gonadotropin‐releasing hormone agonist, highlighting the effectiveness of postoperative adjuvant hormone therapy and supporting a combined surgical and medical approach in the treatment of TES in patients who desire future fertility.